Defeated and Infidel: Two Approaches to the Representation of the Muslim in the Viceroyalty of Peru - Iglesias, Lucila (Eikón / Imago, 2020)
This paper focus on a set of religious images, chronicles and staging relations to research two of the ways in which Muslims were represented in the Andes: as defeated and as infidels. Analyzing some relevant cases in line with both conceptions advances our understandings of the local heritage and resignification of a set of visual and literary resources. Tied to precise senses in the European tradition, those resourses were effective to serve discursive legitimation and preach purposes in the the Peruvian Viceroyalty scenario.